IMPACT OF SOCIAL MEDIA ON PUBLIC RELATIONS PRACTICE - Olayinka, Awofadeju Peter; Philip O. Ewuola (IJRDO - Journal of Social Science and Humanities Research, 2019)
This study examines the impact of social media on public relations practice, using the staff members of Osun State Broadcasting Corporation (OSBC), Osogbo as its population of study. Survey method of gathering data was adopted for this study by distributing well-developed questionnaire to elicit responses from the respondents, the sample size of which was 108. The findings clearly showed that social media platforms like instant messaging, social bookmarking, photo-sharing, wikis, Facebook, etc. have had a great and significant impact on how public relations practitioners communicate as it makes it possible for people and media organizations to have seamless interactions. In addition, social media has enhanced the achievement of public relations objectives by impacting on public relations knowledge, enhancing relationships with people, sharing information on the latest innovations on the tools and methods of public relations, and also helps in shaping the attitude of those in public relations practice.